On the association between microhardness, corrosion resistance and microstructure of probeless friction stir spot welded Al–Li joint - Q. Chu (Journal of Materials Research and Technology, 2021)
The precipitation behavior and development of grain structure have been investigated to reveal their association with the microhardness and corrosion resistance of probeless friction stir spot welded (P-FSSW) joint of an Al–Li alloy. Results identified the primary strengthening phase of T1 (Al2CuLi) to be completely dissolved in the stir zone (SZ), while equiaxed grains were formed. Grain refinement was directly associated with the combined effect of continuous dynamic recrystallization and geometrized effect of imposed strain. However, as localized grain boundary bulging indicated, limited discontinuous recrystallization also participated in the microstructure evolution. The hardness dropped noticeably in the heat affected zone (HAZ) due to the weakening of precipitation and dislocation strengthening, which resulted from partial dissolution or coarsening of T1 phase and recovery effect. Grain refinement and solution strengthening were responsible for the slight increase in hardness of the SZ. In addition, the SZ had minute increased pitting resistance due to the homogenization of intermetallic particles, precipitate dissolution and refined grains.